THE POTENTIAL OF MICROSERVICE ARCHITECTURE FOR INTERNET OF THINGS (IOT) IN SMART CITY, A LITERATURE REVIEW - Hatma Suryotrisongko; Prasasti Karunia Farista Ananto (Universitas Trunojoyo Madura, 2017)
A smart city is a term thatis often used in a literature that refers to a city's intelligence. The visions of smart city are to utilizeits community resources, improving the quality of its services, and reducing the costs for public administration operations. Internet of Things (IoT) is one of the main keys. To accomplish the visions, IoT needs to standardize the technology and web by developing the platform on a large scale. It is a challenge for the city to build widely distributed applications and platforms on the Web. The Microservice Architecture style comes up and offers a lot of convenience and it becomes a new trend for developing Smart City IoT platforms. Before Microservice Architecture, Service Oriented Architecture was previously widely used. To find out Microservice Architecture’s simplicity and potentials, there are two steps to follow: (1) Setting up a Search Strategy on literature review to collect subset of papers with Google Scholar, (2) synthesizing and compiling a subset of literature review to extract data and information to be a literature view. After some reviews of the literatures, most of them agree with the use of microservices architecture in creating or developing a smart city of IoT because the microservices architecture offers a lot and can help the work of IoT smart city developers.